Using scenario modelling for adapting to urbanization and water scarcity: towards a sustainable city in semi-arid areas - Hanoon, Sadeq Khaleefah; Abdullah, Ahmad Fikri; Mohd Shafri, Helmi Zulhaidi; Wayayok, Aimrun (Internacionalni univerzitet u Sarajevu, 2022)
Sustainable development on a global scale has been hindered by urbanization and water scarcity, but the greatest threat is from decision-makers ignoring these challenges, particularly in developing countries. In addition, urbanization is spreading at an alarming rate across the globe, affecting the environment and society in profound ways. This study reviews previous studies that examined future scenarios of urban areas under the challenges of rapid population growth, urban sprawl and water scarcity in order to improve supported decision-making (SDM). Scholars expected that the rapid development of the urbanization scenario would cause resource sustainability to continually be threatened as a result of excessive use of natural resources. In contrast, a sustainable development scenario is an ambitious plan that relies on optimal land use, which views land as a limited and non-renewable resource. In consequence, estimating these threats together could be crucial for planning sustainable strategies for the long term. In light of this review, the SDM tool could be improved by combining the cellular automata model, water evolution and planning model coupled with geographic information systems, remote sensing and Analytic Hierarchy Process (AHP) method. Urban planners could use the proposed tool to optimize, simulate and visualize the dynamic processes of land-use change and urban water to overcome critical conditions.